2016
DOI: 10.4238/gmr.15027822
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 2 protects human umbilical vein endothelial cells against oxidative damage and increases endothelial nitric oxide production to reverse nitroglycerin tolerance

Abstract: ABSTRACT. Medical nitroglycerin (glyceryl trinitrate, GTN) use is limited principally by tolerance typified by a decrease in nitric oxide (NO) produced by biotransformation. Such tolerance may lead to endothelial dysfunction by inducing oxidative stress. In vivo studies have demonstrated that aldehyde dehydrogenase 2 (ALDH2) plays important roles in GTN biotransformation and tolerance. Thus, modification of ALDH2 expression represents a potentially effective strategy to prevent and reverse GTN tolerance and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…ALDH2 protects against heat shock and is involved in the pathogenesis of sepsis (72). ALDH2 overexpression prevented acetaldehydeinduced cell injury and decreased apoptosis in ECs and oxidative stress-induced endothelial dysfunction (73)(74)(75). Alda-1 binds to ALDH2 and restores ALDH activity by acting as a structural chaperone (29).…”
Section: Discussionmentioning
confidence: 99%
“…ALDH2 protects against heat shock and is involved in the pathogenesis of sepsis (72). ALDH2 overexpression prevented acetaldehydeinduced cell injury and decreased apoptosis in ECs and oxidative stress-induced endothelial dysfunction (73)(74)(75). Alda-1 binds to ALDH2 and restores ALDH activity by acting as a structural chaperone (29).…”
Section: Discussionmentioning
confidence: 99%
“…ALDH2 has the highest catalytic efficiency for oxidation of 4-HNE and MDA ( Yoval-Sanchez and Rodriguez-Zavala, 2012 ). ALDH2 functions as a protector against oxidative stress ( Gao et al, 2016 ; Hu et al, 2016b ). Many researchers reported that the levels of MDA and 4-HNE were found to increase in the brain of AD patients ( Khan et al, 2012 ; Zhou et al, 2013 ) and that a sufficient amount of active ALDH2 is needed to detoxify the increased reactive aldehydes that occur in neurodegenerative diseases ( Ohsawa et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…cardiovascular system include acting as the bioactivating enzyme for nitroglycerin and inactivating enzyme for reactive aldehydes removal, which has a great impact on the development of endothelial dysfunction 64,65 (Fig. 1).…”
Section: Sglt2i Protects Aaa Through Antioxidant and Inhibition Of In...mentioning
confidence: 99%
“…Firs, Alda-1 (ALDH2 activator) was shown to attenuate the progression of AAA in a murine model. 62 , 63 Its roles in the cardiovascular system include acting as the bioactivating enzyme for nitroglycerin and inactivating enzyme for reactive aldehydes removal, which has a great impact on the development of endothelial dysfunction 64 , 65 (Fig. 1 ).…”
Section: Overview Of Sglt2imentioning
confidence: 99%